2011
DOI: 10.1016/j.jacc.2010.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of On-Clopidogrel Platelet Reactivity Over Time in Patients Treated With Percutaneous Coronary Intervention

Abstract: In patients at steady state for clopidogrel undergoing percutaneous coronary intervention, PR decreases from baseline to 1 month. Genotype influences ≈18% of this trend. On-clopidogrel PR at 1 month is the strongest predictor of adverse outcomes, and this can be predicted by combining genotype to baseline phenotype and clinical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
216
1
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(252 citation statements)
references
References 19 publications
19
216
1
12
Order By: Relevance
“…Subsequently, a series of publications demonstrated an increased risk for hemorrhagic complications for patients who were carriers or homozygous for the ultrarapid metabolizer allele *17. [20][21][22][23][24][25][26] Our data demonstrate that there are no statistically significant differences in the frequency of poor metabolizer alleles among self-described whites, Hispanics, African American and Ashkenazi Jews. However, Hispanics have a statistically significant lower frequency of the *17 allele than either whites or African Americans.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Subsequently, a series of publications demonstrated an increased risk for hemorrhagic complications for patients who were carriers or homozygous for the ultrarapid metabolizer allele *17. [20][21][22][23][24][25][26] Our data demonstrate that there are no statistically significant differences in the frequency of poor metabolizer alleles among self-described whites, Hispanics, African American and Ashkenazi Jews. However, Hispanics have a statistically significant lower frequency of the *17 allele than either whites or African Americans.…”
Section: Discussionmentioning
confidence: 53%
“…20 Subsequently, several studies including a large meta-analysis have confirmed that the *17 allele is a gain-of-function allele associated with increased activity of clopidogrel and increased risk of hemorrhagic events for patients treated with standard doses of clopidogrel. [21][22][23][24][25][26][27] Estradiol is also metabolized by CYP2C19. In a case-control study of 1,015 patients with breast cancer, women who were taking hormone replacement therapy for more than 10 years and carried a *17 CYP2C19 allele had a decreased risk of breast cancer (odds ratio = 0.57).…”
mentioning
confidence: 99%
“…Recently, Campo et al 39) have reported that more bleeding events occurred in patients undergoing dual antiplatelet therapy with aspirin and clopidogrel after PCI with baseline P2Y12 reactivity units (PRU) of ≤ 85 (n = 15, 20% of patients with PRU ≤ 85) evaluated by VerifyNowP2Y12 (Accumetrics Inc., San Diego, CA) than those with PRU >85 (n = 4, 1.8% of Japanese patients receiving antithrombotic therapy 20) , the annual incidence of life threatening or major bleeding events using the same definition 21) as in the present study was 1.13% in patients treated with aspirin alone, including 60% who had had a prior ischemic stroke. The Cilostazol Stroke Prevention Study II (CSPSII) 34) , a double-blind randomized prospective study, was conducted to compare the clinical outcomes of Japanese patients with a prior ischemic stroke undergoing antiplatelet therapy with aspirin or cilostazol (a phosphodiesterase 3 inhibitor).…”
Section: Incidence Of Macces In Subgroup Of Patients Aged 70 Years Anmentioning
confidence: 98%
“…Five meta-analyses did not include conference abstracts, 5,25,[28][29][30] and all but one of the metaanalyses left out data from one or more full articles that were included in other meta-analyses (Supplementary Table S1 and Supplementary Appendix S1 online). [34][35][36][37][38][39][40][41] For example, the post hoc genetic analysis of the ACTIVE-A trial was included in only two of the seven meta-analyses that did their literature searches after the publication of the trial, 6,24 and one meta-analysis had limited the inclusion to only primary studies with a follow-up time of 6-12 months.…”
Section: -30mentioning
confidence: 99%